Pengaruh Teknologi,Gadget Terhadap Perkembangan Anak - Azizah, Ellisia; Dwi Cahyo Setyono; Salamah Churiyatul Jannah; Hidayatu Munawaroh (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
This article examines the impact of technology use on young children, exploring the role of digital devices in their cognitive, social, and emotional development. While technology provides endless learning opportunities, it is important for parents and educators to understand healthy limits in technology use to support a child's positive growth in the digital age. The development of technology is a challenge for children's development. The use of gadgets for early childhood development can have an impact on the growth and development of young children both physically and mentally.